2016
DOI: 10.1093/nar/gkw572
|View full text |Cite
|
Sign up to set email alerts
|

The role of sequence context, nucleotide pool balance and stress in 2′-deoxynucleotide misincorporation in viral, bacterial and mammalian RNA

Abstract: The misincorporation of 2′-deoxyribonucleotides (dNs) into RNA has important implications for the function of non-coding RNAs, the translational fidelity of coding RNAs and the mutagenic evolution of viral RNA genomes. However, quantitative appreciation for the degree to which dN misincorporation occurs is limited by the lack of analytical tools. Here, we report a method to hydrolyze RNA to release 2′-deoxyribonucleotide-ribonucleotide pairs (dNrN) that are then quantified by chromatography-coupled mass spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…Regardless, the biological relevance of our virus specific observations remains to be investigated; however, it has been reported that RNA viruses are able to incorporate dNTP in their genome. The Dengue virus genome contained on average ~7 DNA residues per genome 35 . Ara-CTP is the triphosphate form of the approved anti-cancer drug cytarabine.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, the biological relevance of our virus specific observations remains to be investigated; however, it has been reported that RNA viruses are able to incorporate dNTP in their genome. The Dengue virus genome contained on average ~7 DNA residues per genome 35 . Ara-CTP is the triphosphate form of the approved anti-cancer drug cytarabine.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, they provide new insights into how dNMP and rNMP substitutions affect the structures of A-RNA and B-DNA. Such substitutions occur in nature as DNA and RNA polymerases misincorporate rNTPs and dNTPs respectively ( 13 , 14 ). Prior NMR studies indicated that isolated rNMPs in DNA duplexes adopt a C3′-endo sugar pucker ( 73 , 74 ).…”
Section: Discussionmentioning
confidence: 99%
“…The resulting A-RNA double helix is also more rigid than its B-DNA counterpart ( 7–9 ). These differences between A-RNA and B-DNA have important biological implications for their recognition by proteins ( 10 , 11 ) and ligands ( 12 ), the templated processes of replication, transcription and translation, the consequences of ribonucleotide and deoxyribonucleotide misincorporation ( 13 , 14 ), and the impact of damage ( 15 ) and chemical modifications.…”
Section: Introductionmentioning
confidence: 99%
“…Total RNA was subsequently extracted with TRIzol following the manufacturer's instructions. The genomic RNA from purified dengue virions was extracted with TRIzol and purified by size-exclusion chromatography as described previously (23,25). The poly(A)-tailed RNA in human CCRF-SB cells was isolated from the total RNA using a Fasttrack MAG Maxi mRNA isolation kit (Life Technologies), whereas the poly(A)-tailed RNA in yeast cells and mouse tissues was isolated from the total RNA using a Dynabeads mRNA Purification kit (Life Technologies) following the manufacturer's protocols.…”
Section: Methodsmentioning
confidence: 99%